A obsolescência como artifício usado pelo fornecedor para induzir o consumidor a realizar compras repetitivas de produtos e a fragilidade do CDC para combater esta prática - Cornetta, William (2017)
The background theme of this work is the consumer society, in particular the obsolescence as a technique applied to products. Considering the disposable consumer context accepted and adopted by the current society, we intend to demonstrate that obsolescence is an artifice used in the production to induce repetitive consumption and at the same time the protective and reparatory mechanisms provided for under the Brazilian Consumer Law (“CDC”) are fragile to protect consumers against such practices. Therefore, it must be understood the artifice of obsolescence in practice and some cases will be used to demonstrate their presence in products placed on the market, from there, analyze the existence of preventive or reparatory mechanisms at the CDC for consumer protection. As methodological support, research adopts the main instruments deductive reasoning and the technical literature. After the introduction, the framework that supports the study develops into seven chapters, specifically for: dealing with consumer society, history, concept and typology of obsolescence, and application of device obsolescence in society according to the typology of Giles Slade (obsolescence technical, psychological obsolescence and planned obsolescence); and confront each obsolescence mode with preventive mechanisms and willing reparatory the CDC to establish the existence or not (brittleness) of consumer protection in this endeavor. The study also collates some specific cases such as the case of Ford vs. General Motors, fashion and design, Phoebus Cartel, Windows and Intel Association, among others. In conclusion, it can be said that obsolescence is the resource or strategy used by many providers to induce consumers to perform repetitive purchases of products motivated by psychological factors, technological, functional or mercadológicos, and the CDC has no preventive mechanisms or robust reparatory for consumer protection against deliberate practice of planned obsolescence